Viscosity drives texture perception of protein beverages more than hydrocolloid type. Issue 1 (6th August 2019) - Wagoner, Ty B.; Çakır‐Fuller, Esra; Shingleton, Rebecca; Drake, MaryAnne; Foegeding, E. Allen
Abstract: Hydrocolloids are added to alter rheological properties of beverages but have other properties that can contribute to overall taste and texture perception. In this study, tapioca starch and λ‐carrageenan were used to determine how hydrocolloid type, viscosity level (4–6 mPa·s, 25–30 mPa·s, and 50–60 mPa·s at 50 s −1 ), and complexity of the system (aqueous, skim milk, or whole milk) influence sensory taste and texture of fluids. All fluids were shear thinning; however, skim milk and whole milk solutions that contained carrageenan had much higher low shear viscosity and lower high shear viscosity than those with starch. There was a significant effect of viscosity level on sensory perception of consistency, creamy/oily, mouthcoating, and residual mouthcoating in aqueous, skim milk, and whole milk beverages, and a weak effect of hydrocolloid type. However, normalizing creamy/oily, paste, and mouthcoating against sensory consistency removed the effect of hydrocolloid type. Flavors (cream, cooked, cardboard, and melon/cardboard) were associated with the type of hydrocolloid and milk protein ingredient. Temporal dominance of sensations showed that samples exhibit similar temporal sensory profiles, although the addition of hydrocolloids enhanced dominance of creaminess even in samples without fat. Hydrocolloid type did not significantly influence mouthcoating or the persistence of astringency. Additionally, increasing viscosity from 3 to 74 mPa·s at 50 s −1 did not suppress perceived sweet or salty taste. The results suggest that in fluid systems with viscosity levels typically found in beverages, textural properties are determined by viscosity and independent of the type of hydrocolloid.